Celebrity shareholders and corporate risk: Based on empirical evidence gathered from Chinese companies listed on the New Third Board - Jingwan Liu; Wei Tang; Xingzhu Zhao (Journal of Applied Economics, 2023)
Using the 2014 to 2019 Forbes China Celebrity Lists, this study empirically examined the relationship between celebrity shareholders and corporate risk. The findings suggest that celebrity shareholders increased corporate risk. And the main reason is that the capital structure of the enterprise changes significantly after the celebrity shares in the enterprise. Furthermore, this study finds that celebrity shareholders had a greater impact on corporate risk among firms with no independent directors, a high proportion of management shareholders, a low proportion of institutional investors and those belonging to the Innovation tier. Based on China's unique cultural and market environment, the findings of this study enrich the literature on the impact of celebrities and corporate risk, revealing the economic consequences of celebrity securitization.
Keywords: 330; Celebrity shareholders; corporate governance; corporate risk; New Third Board